The effectiveness of problem-based learning in improving creative thinking skills, collaborative skills and environmental literacy of Muhammadiyah secondary school students - N. Nurwidodo; Sri Wahyuni; Iin Hindun; Nur Fauziah (Universitas Muhammadiyah Malang, 2024)
This research aimed to analyze the effectiveness of the problem-based learning (PBL) model in improving creative thinking skills, collaborative skills and environmental literacy of Muhammadiyah secondary school (Senior High School and Vocational School) students. The type of research is quasi-experimental. The research design uses Pretest-Posttest Non-equivalent Control Group Design. The experimental research was preceded by a survey regarding the independent and dependent variables, followed by the development of learning tools consisting of a syllabus, student worksheets, creative thinking skills instrument, collaborative skills instrument and environmental literacy instrument. The research sample consisted of 150 grade 10 students taken by total sampling. Data was obtained through observation, questionnaires and tests. The research was conducted from September to December 2023. Analysis of covariance (ANCOVA) was used to verify the data against the proposed hypothesis. The research results show that PBL is effective in improving creative thinking skills, collaborative skills and environmental literacy of Muhammadiyah secondary school students in Batu City. PBL can be implemented widely in an effort to develop creative thinking skills, collaborative skills and environmental literacy.